1985
DOI: 10.1163/156853985x00406
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection in the Spring Peeper, Hyla Crucifer (Amphibia, Anura): Role of the Advertisement Call

Abstract: 1. The advertisement call of the spring peeper exhibits significant variation in each of the four parameters examined: intensity, duration, frequency, repetition rate. 2. In playback experiments involving calls differing in a single parameter, females exhibited preference for loud calls, calls with a rapid repetition rate and low frequency calls. 3. Although we had hypothesized that females would prefer long calls to short calls, they did not. We attribute this lack of preference to unanticipated differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…Finally, the mating system is understood. Both female choice and intermale competition appear to be important elements of courtship (Rosen and Lemon, 1974;Fellers, 1979;Gatz, 1981;Brenowitz et al, 1984;Doherty and Gerhardt, 1984;Forester and Czarnowsky, 1985;Forester and Lykens, 1986). Males of different sizes sometimes employ different mating behaviors (Forester and Lykens, 1986), and males of different sizes sometimes (Gatz, 1981) but not always (Forester and Czarnowsky, 1985) experience different degrees of mating success.…”
mentioning
confidence: 99%
“…Finally, the mating system is understood. Both female choice and intermale competition appear to be important elements of courtship (Rosen and Lemon, 1974;Fellers, 1979;Gatz, 1981;Brenowitz et al, 1984;Doherty and Gerhardt, 1984;Forester and Czarnowsky, 1985;Forester and Lykens, 1986). Males of different sizes sometimes employ different mating behaviors (Forester and Lykens, 1986), and males of different sizes sometimes (Gatz, 1981) but not always (Forester and Czarnowsky, 1985) experience different degrees of mating success.…”
mentioning
confidence: 99%
“…It is suggested that discriminant functions characterised by fundamental frequencies have the potential for male size being encoded in call structure, as seen in anurans [Forester and Czarnowsky, 1985]. To date, frequency variables do not appear to be a good indicator of body size in large mammals [McComb, 1991], and there is considerable and conflicting variation in frequency correlations with adult body size, e.g.…”
Section: Individual Identification From the Long Call And Individual mentioning
confidence: 99%
“…Mate selection by females is mediated primarily by male vocalizations (Forester and Czarnowsky, 1985). In North America, spring peepers are among the first frogs to breed in spring, and their breeding season is prolonged.…”
Section: Study Speciesmentioning
confidence: 99%